Identification of tumor tissue-derived DNA methylation biomarkers for the detection and therapy response evaluation of metastatic castration resistant prostate cancer in liquid biopsies - Dillinger, Thomas; Sheibani-Tezerji, Raheleh; Pulverer, Walter; Stelzer, Ines; Hassler, Melanie R.; Scheibelreiter, Janine; Pérez Malla, Carlos Uziel; Kuroll, Madeleine; Domazet, Sandra; Redl, Elisa; Ely, Sarah; Brezina, Stefanie; et al. (Molecular cancer, 2022)
Aside from genetic alterations, epigenetic tumor-specific changes including DNA methylation are measurable in ctDNA and CTCs and their potential as diagnostic, prognostic and predictive epigenetic biomarkers has been demonstrated in a large number of studies although only few have made it into clinical practice, yet [7]. Next, the 92 analyzed marker candidates were used for prediction model calculations by inputting PMR values for class prediction models based on different algorithms including Diagonal Linear Discriminant Analysis (DLDA), Nearest Centroid Predictor, k-Nearest-Neighbor Predictor, Support Vector Machines and (Bayesian) Compound Covariate Predictor (BCCP/CCP). Together, these data suggest that mCRPC can be identified based on methylation signatures with high accuracy, whereas organ-confined PCa with Gleason scores lower than 9 cannot be differentiated from benign samples, most likely due to limited amounts of ctDNA, which was also described in other studies analyzing DNA methylation in localized PCa patients using digital droplet PCR [11, 12]. When performing fragment analysis of a subset of benign, localized PCa and mCRPC plasma samples (n=20 per group), we observed a significant shift of the mean cfDNA fragment size from 175 bp in benign and localized PCa (range 168 - 183bp) to 168 bp in mCRPC (range 145 – 179 bp) samples (Figure S2I). [...]our markers might be suitable to identify high risk patients, who have already developed micrometastases, which cannot be detected by regular computed tomography (CT).